2013
DOI: 10.1177/1753193413484627
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound diagnosis of ulnar neuropathy: Comparison of symptomatic and asymptomatic nerve thickness

Abstract: There is still no consensus on a normal value for the cross-sectional area of the ulnar nerve at the elbow. Such data would be valuable for the ultrasound diagnosis of ulnar neuropathy. Comparison of the symptomatic and contralateral asymptomatic sides has been recommended. The aim of this study was to investigate whether or not the asymptomatic ulnar nerve could be a reference value. High-resolution ultrasonic measurements of the cross-sectional areas of the ulnar nerves at the elbow were compared with 38 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…The results are comparable to published values for most sites. For example, our result for the CSA of the ulnar nerve in the Guyon canal was 5.0 ± 1.7 mm 2 , and this value is very close to that of Yalcin et al . who found 4.9 ± 0.6 mm 2 and Kerasnoudis et al .…”
Section: Discussionsupporting
confidence: 92%
“…The results are comparable to published values for most sites. For example, our result for the CSA of the ulnar nerve in the Guyon canal was 5.0 ± 1.7 mm 2 , and this value is very close to that of Yalcin et al . who found 4.9 ± 0.6 mm 2 and Kerasnoudis et al .…”
Section: Discussionsupporting
confidence: 92%
“…To overcome these discrepancies, in clinical practice, the healthy contralateral side is often used as an internal control [222324]. Some previous studies described upper limit value of the side-to-side difference [6922]; in addition, one study showed no significant correlation with subjects' baseline demographic factors including age, height, weight, and BMI in CF nerve [9].…”
Section: Discussionmentioning
confidence: 99%
“…Although ΔSx–Asx was a useful and reliable value, it is not applicable to bilateral lesions or diffuse nerve pathology [222324]. Therefore, the ratio of nerve CSA has also been analyzed and proposed as a complementary value [252627].…”
Section: Discussionmentioning
confidence: 99%
“…There has been debate in the literature about use of the asymptomatic contralateral limb as an internal control . Also noteworthy is that time may erode the CSA size/nerve‐injury‐severity relationship.…”
Section: Discussionmentioning
confidence: 99%